(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
Rural communities are possessors of a great cultural wealth. In this sense, in the Andean rural area, ancestral practices are preserved that contain a knowledge of spaces and a wisdom regarding nature. In this sense, transhumance is considered as the activity that still prevails in the Zhamar community, and is carried out by Mr. Damián Morocho and his mother Rosa Carchi. Every 4 months they undertake a trip with all their cattle to the foothills of the Nabón canton to provide food for their animals, an essential aspect of their economy. This practice, although it is still practiced in certain cases, is diffi cult and requires physical and mental effort for those who carry it out, and knowledge of the destination mountains.